Makna Perintah dalam Al-Qur’an Surah Yūsuf - Haikal, Muhammad Ichsan; Jannah, Nur Roudhatul (Al-Ma‘rifah, 2021)
This study aims to determine how much the imperative sentences (amr) is used, its meaning, and its purpose in surah Yūsuf. This study uses a qualitative descriptive method that describes the existing data. The data is obtained from the verses of the Quran surah Yūsuf, which contains the commandment sentences. The results of this study indicate that in surah Yūsuf there are 32 command sentences, namely in verses 9(2), 10, 12, 21, 23, 29(2), 31, 36, 42, 43, 46, 50(2), 54, 55, 59, 62, 63, 67, 78, 81(2), 82, 87, 88, 93, 97, 99, 101, and 108. The results of the 32 data show 31 in the form of fi‘l amr and 1 in the form of isim fi‘l amr. Then, of the 32 command sentences, there are 19 which have an essential command meaning. In addition, there are some deviations in the meaning of the command sentences in surah Yūsuf, (1) the meaning of irshād, found in verses 29, 50, and 67; (2) the meaning of takhyīr in verse 9; and (3) the meaning of prayer (du‘ā’) in verses 12, 55, 63, 78, 88, 97, and 101.